PENERAPAN MODEL PEMBELAJARAN RADEC (READ, ANSWER, DISCUSS, EXPLAIN, CREATE) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM: PENELITIAN EKSPERIMEN DI KELAS X A SMA CILEDUG AL-MUSADADDIYAH GARUT - Ikrima, Widi Fuzi Widayanti; Amirudin , Ja’far; Usman , Asep Tutun (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
The background of this research is to examine the learning outcomes of PAI (Islamic Religious Education) students who do not reach the KKM. This research aims to improve student learning outcomes in Islamic Religious Education (PAI) subjects in class X SMA Ciledug Al-Musadaddiyah Garut by implementing RADEC learning (Read, Answer, Discuss, Explain, Create). In class. The instrument used in this research is a multiple choice test and is divided into two pretest and posttest in order to see an increase in student learning outcomes. Based on research results, student learning outcomes after implementing Pretest got an average score of 68 while after carrying out posttest get an average value of 85. The estimated T is 14.72 and the T table is 2.69 with db = 48, = 0.01 and checked with a one-party test, showing that the calculated T is outside the HO area, in accordance with the findings hypothesis test calculations. By using RADEC learning (Read, Answer, Discuss, Explain, Create), compared to traditional approaches, student learning outcomes will increase significantly